Multinational Corporation (MNC) as foreign policy actor: a case study on Petroliam Nasional Berhad (PETRONAS) / Ahmad Shafez Adil - Adil, Ahmad Shafez (Faculty of Business and Management, 2009)
Petroliam Nasional Berhad (PETRONAS) is a Malaysia’s leading oil and gas multinational company. From the establishment of the company on August 17th, 1974 until recent year, its contribution in term of dividends, royalties, and export duties are getting increased. This study is to identify the role of Multinational Corporation (MNC), in this case PETRONAS in international arena in term of economic and politics. Do they practice the foreign policy that formulated by the government of Malaysia.